Effect of Nebulized Eucalyptus on Ventilator Associated Pneumonia in Ventilated Patients - Nazanin Amini; Korosh Rezaei; Mehdi Bahrami; Ahmadreza Yazdannik (Institue of Medicinal Plants, ACECR, 2019)
Background: Ventilator associated pneumonia (VAP) is a common nosocomial infection among patients admitted in ICUs. It results in prolonged intensive care unit (ICU) stay, excess healthcare costs, and higher mortality. Objective: This study aims to assess the effect of nebulized eucalyptus (NE) on ventilator associated pneumonia in ventilated patients. Method: We performed a randomized clinical trial study in three intensive care units of educational hospital. Seventy intubated patients that likely required mechanical ventilation for more than 72 hours were selected through purposive sampling and randomly divided into NE (n = 35) and Placebo (n = 35) groups. NE group received 4 ml (5%) eucalyptus in 6 ml normal saline (NS) every 8 h. Placebo group received only 10 ml NS in the same way. At the fifth, ninth day and before extubation VAP was diagnosed through modified clinical pulmonary infection score (MCPIS). Results: VAP was found in 11 (31.4%) patients receiving NE and in 23 (65.7%) patients in the control group (P = 0.004). The median of duration of intubation in study population was 9.4 ± 3.75 (3-14 day) (P = 0.13). Patients with pneumonia had longer intubation than non-infected patients (P = 0.001). Conclusion: NE can reduce ventilator associated pneumonia in ventilated patients.